ARAHAN PRODUK PARIWISATA PERDESAAN DI DESA WISATA EKASARI KABUPATEN JEMBRANA PROVINSI BALI - Adikampana, I.M.; Pujani, L.P.K; Sanjiwani, P.K. (Buletin Udayana Mengabdi; Vol 20 No 3 (2021): Buletin Udayana Mengabdi, 2022)
Ekasari Tourist Village is a prominent rural tourism destination in Jembrana Regency, Bali. The village has the resources for religious tourism, agro-tourism, and water-based tourism. However, the development of tourism has not obtained a significant intention from the market. This situation is led by the limited understanding of the local community towards the development of rural tourism products that are related to the needs of the target market. Therefore, a community engagement program is needed regarding guidance of rural tourism products for the community in the Ekasari Tourist Village. Such a program is carried out by holding counseling with the theme of rural tourism product planning and development. This program is targeted selected local community groups, that is Pokdarwis, youth and women's groups. The presence of guidance on rural tourism products makes the local community able to create quality attractions, amenities, and accessibility and is able to compete with other rural tourism destinations. Keywords: guidance, tourism products, Ekasari Tourist Village